Observations of Modified Warm Deep Water Beneath Ronne Ice Shelf, Antarctica, From an Autonomous Underwater Vehicle - Davis, Peter E. D.; Jenkins, Adrian; Nicholls, Keith W.; Dutrieux, Pierre; Schröder, Michael; Janout, Markus A.; Hellmer, Hartmut H.; Templeton, Rob; McPhail, Stephen (Journal of geophysical research. Oceans, 2022)
Filchner‐Ronne Ice Shelf (FRIS) is the world's largest ice shelf by volume. It helps regulate Antarctica's contribution to global sea level rise, and water mass transformations within the sub‐ice‐shelf cavity produce globally important dense water masses. Rates of ice shelf basal melting are relatively low, however, as the production of cold (−1.9°C) and dense High Salinity Shelf Water over the Weddell Sea continental shelf isolates the ice shelf from large‐scale inflow of warm water. Nevertheless, a narrow inflow of relatively warm (−1.4°C) Modified Warm Deep Water (MWDW) that hugs the western flank of Berkner Bank is observed to reach Ronne Ice Front, although the processes governing its circulation and fate remain uncertain. Here we present the first observations taken within the ice shelf cavity along this warm water inflow using the Autosub Long Range autonomous underwater vehicle. We observe a core of MWDW with a south‐westward velocity of 4 cm s−1 that reaches at least 18 km into the sub‐ice cavity. The hydrographic properties are spatially heterogeneous, giving rise to temporal variability that is driven by tidal advection. The highest rates of turbulent dissipation are associated with the warmest MWDW, with the vertical eddy diffusivity reaching 10−4 m2 s−1 where the water column is fully turbulent. Mixing efficiency is close to the canonical value of 0.2. Modeling studies suggest MWDW may become the dominant water mass beneath FRIS in our changing climate, providing strong motivation to understand more fully the dynamics of this MWDW inflow. Plain Language Summary Filchner‐Ronne Ice Shelf is the largest floating extension of the Antarctic Ice Sheet by volume. The ocean beneath it is cold and dense, and thus little ocean‐driven melting occurs at its base. Climate models predict that a significant shift in ocean circulation within the sub‐ice‐shelf cavity may occur within the coming century, with large‐scale inflows of warm water, highly elevated basal melt rates, and significant consequences for global sea level rise. Understanding the complex ice‐ocean interactions that occur beneath Filchner‐Ronne Ice Shelf is therefore critical. At present, only a single, narrow inflow of warm water is observed along Ronne Ice Front. The processes controlling this warm inflow are poorly understood, and here we present the first observations from the inflow region obtained using the unique autonomous Autosub Long Range underwater vehicle. We observe that the flow of warm water into the cavity extends at least 18 km and is highly patchy in nature, with isolated maxima in ocean temperature that are moved around by the tides. Vertical mixing is strongest where the ocean is warmest, contributing to diffusing and eroding the warm water signature. Many questions remain, motivating further studies with both autonomous and traditional observing platforms. Key Points First observations with an Autonomous Underwater Vehicle beneath Ronne Ice Shelf, Antarctica, along the Modified Warm Deep Water inflow path The inflow velocity averages 4 cm s−1, and the hydrographic properties show strong spatial variability that is subject to tidal advection Turbulent mixing is elevated for the warmest Modified Warm Deep Water, with eddy diffusivity values reaching 10−4 m2 s−1